Proceedings of 1994 28th Asilomar Conference on Signals, Systems and Computers
DOI: 10.1109/acssc.1994.471505
|View full text |Cite
|
Sign up to set email alerts
|

Static scheduling and code generation from dynamic dataflow graphs with integer-valued control streams

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 11 publications
0
46
0
Order By: Relevance
“…Although CFDF is significantly restricted compared to EIDF, it is highly expressive as a deterministic dataflow model of computation. Indeed, it has been shown that Boolean dataflow actors [4] can be transformed into functionally equivalent CFDF actors [20]. From such a transformation and the established Turing completeness of Boolean dataflow, it can be demonstrated that CFDF is also Turing complete.…”
Section: Enable-invoke Dataflowmentioning
confidence: 99%
“…Although CFDF is significantly restricted compared to EIDF, it is highly expressive as a deterministic dataflow model of computation. Indeed, it has been shown that Boolean dataflow actors [4] can be transformed into functionally equivalent CFDF actors [20]. From such a transformation and the established Turing completeness of Boolean dataflow, it can be demonstrated that CFDF is also Turing complete.…”
Section: Enable-invoke Dataflowmentioning
confidence: 99%
“…The natural solution to this is to place the transformation mechanism in between the application and architecture models, that is, in Sesame's mapping layer. As shown in Figure 4.1, trace transformations which transform application event traces into (more refined) architecture event traces are realized by refining the virtual processor components in Sesame with Integer-controlled dataflow (IDF) [16] graphs. However, before going into details of IDF-based trace transformations, we first formalize traces and their transformations mathematically in the next section.…”
Section: Dataflow-based Trace Transformationsmentioning
confidence: 99%
“…The only way to improve this is to improve the mapping strategy. In Sesame, we make use of Integer-controlled Dataflow (IDF) graphs [16] at the mapping layer for this purpose. With the introduction of IDF graphs for mapping, we move from the traditional TD approach to a new mapping strategy which we call the Enhanced Trace Driven (ETD) approach [38].…”
mentioning
confidence: 99%
“…Boolean dataflow [41,43] (BDF) and integer-controlled dataflow [44] (IDF) augment the model by permitting the number of tokens produced or consumed at a port to be symbolically represented by a variable. The value of this variable is permitted to change during execution, so datadependent control flow can be represented.…”
Section: Decidable Dataflow Modelsmentioning
confidence: 99%